New directions in building a scientific social network: Experiences in the Supercourse project and application to Central Asia - Meredith Hennon; Ronald E. LaPorte; Eugene Shubnikov; Faina Linkov (University Library System, University of Pittsburgh, 2012)
Introduction Networking leaders in the field of public health and medicine is very important for improving health locally and globally, especially in times of disaster. Methods Fishing can best be defined as using an internet search engine to find the name and email address of the person or organization that is being sought. Results With over 500 hours of work, the group compiled a list of nearly 2,000 email addresses of Ministers of Health, deans of the 1,800 medical schools and schools of public health, and heads of medical and public health societies. Conclusions Fishing for deans and others is an important task, albeit just the first step in building a scientific social network.  Upon creation of a database of names, other steps must be taken, such as meeting with others, exchanging information, and forming new collaborations before a scientific social network is successfully completed.